The impact of Moodle-Assisted activities for Vocabulary recycling on EFL Grade-11 vocabulary retention : - Nguyễn, Tuấn Hải (Trường đại học Cần Thơ, 2019)
This experimental study was conducted in order to measure the impact of Moodle-assisted activities for vocabulary recycling on EFL grade-11 students’ vocabulary retention. Having collected the study data, the results of the study ere further analyzed to observe 1) to what extent do Moodle-assisted multiple activities for vocabulary recycling enhance Ss’ vocabulary retention, and 2) what the effect size of Moodle-based vocabulary quiz was when vocabulary retention is considered.